Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Agile leadership among the leaders of public primary schools in Unayzah Governorate from the point of view of the teachers Hailah Mandeel Al-Towaijri, Sohad Abdulrahman Al-Buraikan, Hind Khalifah Al-Khalifah, Maram Rumaih Al-Romaihi 2. Requirements for Employing Augmented Reality Technology in Blended Learning Environment by English Teachers in Light of Innovations Dissemination Theory Fatima Saleh Alharthi, Hala Ibrahim Hassan 3. The mental image of vocational education for tenth grade students in public schools in Tulkarem Governorate Nuha Ismail Iter, Alaa Mahmoud Hijaz 4. The degree to which female teachers of the first three grades in Zarqa first employ alternative assessment tools from their own point of view Munera Ahmad Abed Alasad 5. Mindfulness and Cognitive Flexibility as Predictors of Academic Self-Efficacy among Umm Al-Qura University Female Students Hatun Ibrahim Saad Alharbi, Nawar Mohammed Saad Alharbi 6. Effectiveness of the Memory and Attention Battery in the Leiter-3 Scale in Diagnosing Attention Deficit and Hyperactivity Disorder (ADHD) Zain Akram Abu Laban, Ahmad Mahmoud Thawabieh 7. The commitment of educational counselors in Irbid governorate to the standards of the American Association for Counsellors Mohammad Mahmoud Mayas, Hanan Ibrahim Al-Shaqran